10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Few data inform implementation of emerging state-regulated psilocybin programs. OBJECTIVE: The Open Psychedelic Evaluation Nexus (OPEN) aims to assess the safety and participant outcomes of Oregon's regulated psilocybin services. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included psilocybin clients enrolled between November 2024 and March 2026, with follow-up through June 2026, at 24 of 26 Oregon psilocybin service centers with active licenses. Eligible participants were consenting Oregon psilocybin services clients supervised by 83 licensed psilocybin facilitators. OPEN's client-facing platform collects confidential data at baseline and at 1 week, 1 month, and 3 months after psilocybin sessions supported by licensed facilitators. EXPOSURE: Receipt of Oregon psilocybin services. MAIN OUTCOMES AND MEASURES: Facilitator-reported psilocybin dose (in milligrams) and safety events during psilocybin session. Participant-reported depression (measured by the Participant Health Questionnaire-9), anxiety (Hospital and Anxiety Depression Scale), and PTSD (6-item PTSD Checklist [PCL-6]) symptoms; mental well-being; life satisfaction; harms; overall benefit; meaning; and services satisfaction. RESULTS: A total 346 participants were included (mean [SD] age, 49.5 [13.4] years; 181 women [52.5%]; 15 Asian [4.3%], 300 White [86.7%], 12 multiple races [3.5%]); 19 participants (5.5%) identified as veterans, 262 (76.6%) completed college, and 89 (29.0%) had a household income above $200 000. Reported substance use in the past 30 days was 203 (58.7%) for alcohol, 38 (11.0%) for nicotine or tobacco, and 127 [36.7%] for cannabis use; 44.2% were psychedelic-naive and received a mean (SD) psilocybin dose of 31.9 (11.2) mg. Retention was 93.1% at 1 week (322 participants), 92.8% at 1 month (321 participants), and 90.2% at 3 months (312 participants). Four individuals (1.2%, all psychedelic-naive) experienced adverse behavioral reactions requiring medical attention. Few participants reported their psilocybin experience as harmful (5 of 305 [1.6%] at 1 week, 6 of 321 [1.9%] at 1 month, and 7 of 312 [2.3%] at 3 months). At 1 month, 92.2% (296 of 321 participants) felt they benefited, and 58.6% (188 of 321 participants) ranked the experience among the 10 most meaningful of their life. At 3 months, participants reported decreased moderate-to-severe symptoms of depression (relative risk [RR], 0.40; 95% CI, 0.32-0.50), anxiety (RR, 0.29; 95% CI, 0.22-0.38), and PTSD symptoms (RR, 0.35; 95% CI, 0.27-0.45), and improved mental well-being (mean difference in Short Warwick-Edinburgh Mental Well-being Scale = 3.21; 95% CI, 2.66-3.76), and life satisfaction (RR, 1.31; 95% CI, 1.19-1.44) compared with baseline. Serious adverse reactions were uncommon, although at rates that were statistically significant. CONCLUSIONS AND RELEVANCE: In this multisite cohort of participants receiving state-regulated psilocybin services in Oregon, serious adverse reactions were uncommon. Most participants reported improvements in mental health, wellness, and life satisfaction. Longitudinal findings support safety and potential benefits that can inform clinicians, policymakers, and the public as other state-regulated psychedelic services emerge.